Nonstabilized SARS-CoV-2 spike mRNA vaccination induces broadly neutralizing antibodies in nonhuman primates - Malewana, R Dilshan; Stalls, Victoria; May, Aaron; Lu, Xiaozhi; Martinez, David R; Schäfer, Alexandra; Li, Dapeng; Barr, Maggie; Sutherland, Laura L; Lee, Esther; Parks, Robert; Beck, Whitney Edwards; et al. (Science translational medicine, 2025)
Immunization with messenger RNA (mRNA) or viral vectors encoding spike protein with diproline substitutions (S-2P) were shown to provide protective immunity, curbing the COVID-19 pandemic. However, in light of the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern (VOCs) that can cause COVID-19, it is essential that we understand how immunization with spike protein elicits neutralizing antibodies (nAbs). Here, we compared immunization of macaques with mRNA vaccines expressing ancestral spike protein with or without diproline substitutions, showing that the diproline substitutions were not required for protection against SARS-CoV-2 challenge or induction of broadly neutralizing B cell lineages. One group of nAbs elicited by the ancestral spike protein lacking diproline substitutions targeted the outer face of the receptor binding domain (RBD), neutralized all tested SARS-CoV-2 VOC pseudotyped viruses including Omicron XBB.1.5 in vitro, but lacked cross-sarbecovirus neutralization. Structural analysis showed that the macaque nAbs that could broadly neutralize VOCs bound to the same epitope as a human nAb, DH1193. In contrast, vaccine-induced antibodies that targeted the RBD inner face neutralized multiple sarbecoviruses, protected mice from bat CoV RsSHC014 challenge, but lacked Omicron variant neutralization. Thus, ancestral SARS-CoV-2 spike mRNA vaccines lacking proline substitutions can induce B cell lineages binding to distinct RBD sites that either broadly neutralize animal and human sarbecoviruses or neutralize recent Omicron VOCs. Thus, the use of a nonstabilized spike protein design in some COVID-19 vaccines does not preclude the elicitation of broad sarbecovirus and broad VOC nAbs.